Physicians in 21st century healthcare: developing physician leaders for the future - Smith, Kimberly A. (Kansas State University, 2014)
This bounded case study explored ten purposefully selected physician participants’ perceptions of the effectiveness of an eight session, two year in-house physician leadership development program at a major Academic Medical Center (AMC) in the Midwest. While physicians are generally educated to care for patients in their specialty area, reforms necessitate the need for physician leadership involvement in metric tracking by healthcare organizations in order to provide a focus on quality patient care and safety. Participants indicated finding the course effective, especially the negotiations and finance modules. These modules provided new language, a better understanding of processes and an opportunity to develop skills through interactive class exercises such as case studies. Participants described an increased self-awareness of their interpersonal skills and expressed a desire for greater exposure to emotional intelligence principles. Participants experienced a transformational shift in how they constructed their identity as a physicians and leaders, and questioned assumptions about the physician’s role in healthcare. While effective in initiating a process of exploration, this course was not sufficient to meet the goals and objectives of the program. Therefore, recommendations for the advanced course included a focus on leadership competencies identified by Dye and Garman (2006) as cited by Dye and Sokolov (2013), emotional intelligence, and transformational leadership.
Keywords: Physicians leadership development; Adult Education (0516); Educational leadership (0449); Health Education (0680); Higher Education (0745)